Optimal design for concrete pavement situated above box culvert: experimental and numerical study. Issue Volume 18:Issued 5(2017) (4th May 2017) - Park, Joo-Young; Sohn, Dueck-Su; Lee, Jae-Hoon; Song, Ki-Il; Jeong, Jin-Hoon
Abstract: This study examined the pavement distress data obtained from the field as well as the effects of the soil cover depth, joint position and reinforced slab length on the behaviour of concrete pavement using the finite element method. An ultimate strength model with a similarity of 1/2 was designed and constructed. Finite element analysis incorporating an implicit direct numerical integration scheme was conducted to obtain an optimal design for the pavement structure above a box culvert. An accelerated pavement test was conducted for validation, in which a realistic traffic load was imposed on the pavement model constructed in the laboratory. The strain histories were measured at each section and compared with those of numerical analysis. The optimal joint position and reinforced slab length that can minimise the damage to the pavement structure above a box culvert were also determined.